Transcriptomic Profiling Reveals Shared Signalling Networks Between Flower Development and Herbivory-Induced Responses in Tomato - Ke, Lanlan; Wang, Yangzi; Schäfer, Martin; Städler, Thomas; Zeng, Rensen; Fabian, Jörg; Pulido, Hannier; De Moraes, Consuelo M.; Song, Yuanyuan; Xu, Shuqing (Frontiers in Plant Science, 2021)
Most flowering plants have to defend themselves against herbivores for survival and attract pollinators for reproduction. Although traits involved in plant defence and pollinator attraction are often localised in leaves and flowers, respectively, they will show a diffuse evolution if they share the same molecular machinery and regulatory networks. We performed RNA-sequencing to characterize and compare transcriptomic changes involved in herbivory-induced defences and flower development, in tomato leaves and flowers, respectively. We found that both the herbivory-induced responses and flower development involved alterations in jasmonic acid signalling, suppression of primary metabolisms and reprogramming of secondary metabolisms. We identified 411 genes that were involved in both processes, a number significantly higher than expected by chance. Genetically manipulate key regulators in induced defences also led to the expression changes in the same genes in both leaves and flowers. Targeted metabolomic analysis showed that among closely related tomato species, jasmonic acid and α-tomatine are correlated in flower buds and herbivory-induced leaves. These findings suggest that herbivory-induced responses and flower development share a common molecular machinery and likely have coevolved in nature.